The Representation of Social Actors in Corporate Codes of Ethics. How Code Language Positions Internal Actors - Winkler, Ingo (2011)
This article understands codes of ethics as written documents that represent social actors in specific ways through the use of language. It presents an empirical study that investigated the codes of ethics of the German Dax30 companies. The study adopted a critical discourse analysis-approach in order to reveal how the code-texts produce a particular understanding of the various internal social groups for the readers. Language is regarded as social practice that functions at creating particular understandings of individuals and groups, how they are interrelated, and how they should behave. Findings show that codes of ethics do not represent employees as a group that is empowered or morally enlightened; instead they are positioned as passive receivers of rules and regulations. Furthermore, codes of ethics classify employees as having a need to be monitored and controlled by the higher levels of the corporate hierarchy. Overall, code language enforces compliance through maintaining existing and building new asymmetries between the different groups within a company. As a consequence, the article discusses a somewhat different understanding of code effectiveness. Reproducing and reemphasizing hierarchical relations could also lead to code compliance, perhaps without any need for developing the moral employee that is committed to ethical values.
Keywords: Germany; Discourse; Language; actor positioning; Representation; code effectiveness; codes of ethics